Nanostructural evidence of mechanical aging and performance loss in ballistic fibers. Issue 23 (28th September 2017) - Howarter, John A.; Liu, Ming; McDonough, Walter G.; Soles, Christopher; Holmes, Gale A.
ABSTRACT: It is understood that the ballistic resistance of aromatic polyamide fibers is related to the fiber's ultimate tensile strength, strain‐to‐failure, and Young's modulus. Ideal high‐performance ballistic materials maximize these properties while minimizing material density. Equally important is long‐term mechanical and chemical stability: the fibers should not exhibit performance loss over their lifetime. However, less is known quantitatively about their modes of degradation, and experimental methods to quantify the aging and degradation in these fibers are critical. Multiple variations of next generation high‐performance fibers have been investigated under chemical and mechanical accelerated aging conditions. Performance losses have been empirically correlated to chemical degradation of the polymer chain and nanostructural changes in the fiber morphology through X‐ray photoelectron spectroscopy (XPS). Here, we introduce positron annihilation lifetime spectroscopy measurements as a sensitive method to quantify the early onset of damage in the flexed fibers as quantified through changes in the nanoscale void structure in the material. Published 2017. † J. Polym. Sci., Part B: Polym. Phys.2017, 55, 1711–1717 Abstract : Methods of rapidly assessing aging and degradation of high performance polymer fibers are critical for designing next‐generation materials. Three polymer fiber types were investigated under accelerated aging conditions. Single fiber tensile behavior of the aged samples varied based on the chemical and nanostructural composition of the fibers. Fiber nanostructure was characterized with positron annihilation lifetime spectroscopy to measure the onset of changes in free volume and void formation.